Perlindungan Hukum Bagi Penghadap Penyandang Disabilitas Dalam Pembuatan Akta Notaris - Firmansyah, Melania Indiana Putri (PT Matra Cendikia Abadi, 2024)
Legal protection for persons with disabilities in the preparation of notary deeds involving land disputes, with a focus on the analysis of Supreme Court Decision Number 1263 K/Pdt/2021. Notaries have a responsibility to ensure that the deeds they make meet the formal and material provisions, especially when it involves persons with disabilities who are vulnerable to potential manipulation or legal errors. This study uses normative juridical methods through a legislative and case approach, by examining the preventive and repressive aspects of the legal protection of persons with disabilities in notary practice. The results of the analysis show that there is the implementation of legal protection for persons with disabilities in notarial practice still faces various significant obstacles, including limited infrastructure, lack of notary competence in serving persons with disabilities, and the absence of standardization of special service procedures. The preventive aspect includes the obligation of notaries to ensure the understanding of the parties, provide accessibility, and verify legal capacity without discrimination. Meanwhile, the repressive aspect is manifested in the dispute resolution mechanism and adequate legal assistance for persons with disabilities. Supreme Court Decision Number 1263 K/Pdt/2021 has emphasized the importance of fulfilling formal and material aspects in making notarial deeds involving persons with disabilities, especially regarding the obligation to read the deed and the presence of witnesses. This decision is an important jurisprudence that strengthens legal protection for persons with disabilities in notarial practice and emphasizes the responsibility of notaries in providing services that pay attention to the special needs of persons with disabilities. Systematic efforts are needed in the form of improving notary competence, developing accessible infrastructure, and strengthening the supervision system to optimize the implementation of this legal protection. Keywords : Legal Protection; Disabilities; Notary’s Deed